In vitro reconstitution of a heterotrimeric nucleoporin complex consisting of recombinant Nsp1p, Nup49p, and Nup57p. - Schlaich, Nikolaus; Häner, Markus; Lustig, Ariel; Aebi, Ueli; Hurt, Ed (Molecular biology of the cell, 1997)
The yeast nucleoporins Nsp1p, Nup49p, and Nup57p form a complex at the nuclear pores which is involved in nucleocytoplasmic transport. To investigate the molecular basis underlying complex formation, recombinant full-length Nup49p and Nup57p and the carboxyl-terminal domain of Nsp1p, which lacks the FXFG repeat domain, were expressed in Escherichia coli. When the three purified proteins were mixed together, they spontaneously associated to form a 150-kDa complex of 1:1:1 stoichiometry. In this trimeric complex, Nup57p fulfills the role of an organizing center, to which Nup49p and Nsp1p individually bind. For this interaction to occur, only two heptad repeat regions of the Nsp1p carboxyl-terminal domain are required, each region being about 50 amino acids in length. Finally, the reconstituted complex has the capability to bind to full-length Nic96p but not to mutant forms which also do not interact in vivo. When added to permeabilized yeast cells, the complex associates with the nuclear envelope and the nuclear pores. We conclude that Nsp1p, Nup49p, and Nup57p can reconstitute a complex in vitro which is competent for further assembly with other components of nuclear pores.